Do high-risk investors matter in online P2P lending market? Evidence from China - Manping Tang; Kailang Zhu; Xinghong Li; Wei Yang (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The development of network technology has prompted the gradual rise of lending platforms, which not only meet the borrowing needs of the long-tail population, but also provide new investment methods for investors with idle funds. However, behind the rapid development of P2P online lending is accompanied by increasingly prominent risk issues. Using a Probit model and a dataset of 337,634 loan listings from a leading Chinese online Peer-to-Peer (P2P) lending platform (i.e., Renrendai platform), we investigate whether high-risk investors contribute to online P2P loan default risks and interest rates. Our empirical results show that, with 1% increase in the percentage of high-risk investors in a loan, the likelihood of loan default would increase by 0.79% and the loan's interest rate would increase by 4%. Our analysis suggests that the percentage of high-risk investors should be considered in online P2P lending risk management. To the best of our knowledge, this is the first paper to study the impact of fund providers' risk attitude on the online P2P lending market
Keywords: 330; P2P lending; high-risk investors; default risks; interest rates; China